Occupational psychosocial risks as predictors of depression, anxiety, and stress among hospital employees - Aaron Siong Fatt Tsen; Khamisah Awang Lukman; Mohammad Saffree Jeffree; Syed Shajee Husain; Izzul Syazwan Ismail (PLoS ONE, 2026)
Workplace mental health is a growing concern in Malaysia’s healthcare sector, yet comprehensive psychosocial risk assessments across all staff remain limited. This cross-sectional study examined the prevalence and predictors of depression, anxiety, and stress among employees in four government tertiary hospitals in Kota Kinabalu, namely Hospital Queen Elizabeth, Hospital Queen Elizabeth II, Hospital Wanita dan Kanak-Kanak Sabah, and Hospital Mesra Bukit Padang. From 21 st March 2025–20 th April 2025, 233 staff members were selected via stratified random sampling. Data were collected using validated self-administered online questionnaires, including the 21-item Depression, Anxiety and Stress Scale and the Likelihood of Environment & Occupational Exposure Scale towards Psychosocial Risk in the Workplace. Analyses involved descriptive statistics, bivariate comparisons, and multivariate logistic regression using SPSS version 29. Results revealed high prevalence rates of anxiety (43.8%), depression (37.8%), and stress (27.0%). Bivariate analysis revealed elevated odds of depression among Chinese ethnicity, diploma educated, high-income staff, HQE employees, medical and clinical roles, doctors, and shift workers. Anxiety was linked to medical departments and shift work, while stress was prevalent in younger staff with shorter tenure. High job demand, low control, and inadequate support increased depression, anxiety, and stress risk. Multivariate analysis identified high psychosocial risks related to job demand (OR 3.94), control (OR 3.72), and support (OR 2.87) as significant predictors of depression. High psychosocial risk in job demand (OR 3.01), control (OR 2.29), and support (OR 2.59) also predicted anxiety. Stress was closely linked to staff aged 20–39 years (OR 3.14), high psychosocial risk in job control (OR 4.45), and support (OR 2.68). Although the cross-sectional design and reliance on self-report limit causal interpretation, these findings highlight the value of regular psychosocial risk assessments and targeted interventions. Strengthening workplace support systems is crucial to improving mental well-being among Malaysia’s hospital workforce.